2001
DOI: 10.1109/10.959328
|View full text |Cite
|
Sign up to set email alerts
|

Concentric-ring electrode systems for noninvasive detection of single motor unit activity

Abstract: New recording techniques for detecting surface electromyographic (EMG) signals based on concentric-ring electrodes are proposed in this paper. A theoretical study of the two-dimensional (2-D) spatial transfer function of these recording systems is developed both in case of rings with a physical dimension and in case of line rings. Design criteria for the proposed systems are presented in relation to spatial selectivity. It is shown that, given the radii of the rings, the weights of the spatial filter can be se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 30 publications
4
60
0
1
Order By: Relevance
“…The behaviors of the isotropic detection systems as a function of the ber orientation were also examined [13]. However, the sensitivity of the BiTDD [14] and the MKF [15] systems to the muscle ber orientation has never been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behaviors of the isotropic detection systems as a function of the ber orientation were also examined [13]. However, the sensitivity of the BiTDD [14] and the MKF [15] systems to the muscle ber orientation has never been examined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that highly anisotropic, approximately isotropic [11,12] and isotropic systems [13] are very sensitive [12], less sensitive [11,12] and not sensitive [13], respectively, to the muscle ber direction. A comparative study showed that amplitude and spectral variables of surface EMG signals are less affected by the ber direction if almost isotropic detection systems are used than if anisotropic ones are used [1].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, past research efforts in the surface EMG field were mainly devoted to the development of processing techniques in time and frequency domain, which gave indications about the global EMG activity, without aiming at an analysis at the single MU level. Although, recently, techniques for noninvasive assessment of single MU properties have been proposed and refined (4,6,8), their applicability is still limited by the need of complex detection systems, to low-contraction levels, and controlled laboratory conditions for signal recording. Thus the extraction of global information from the surface EMG signal remains of paramount importance in many applications, such as sport and occupational medicine, rehabilitation, and basic and applied physiology.…”
mentioning
confidence: 99%
“…In the present study during both BHM and SIM, power spectrum of Laplacian EMGdi signal was more distributed in frequency, contained in a broader frequency range compared to bipolar EMGdi power spectrum. Because of their physical design, Laplacian electrode presents enhanced spatial selectivity, features which are reflected in its spatial transfer function [12]. The use of a Laplacian electrode in sEMG recordings can improve the study of motor unit action potential trains [12,13] and reduce the problem of location and orientation of the fibers related to the use of bipolar disc electrode configuration [12].…”
Section: Resultsmentioning
confidence: 99%